KNEE ARTHRODESIS USING ILIZAROV: WHEN TO USE? - Tarmuzi, Nazari Ahmad (International Journal of Allied Health Sciences, 2021)
The Illizarov method offers a comprehensive approach for dealing with chronic knee infection, traumatic bone loss and knee joint destruction by using knee compression arthrodesis with or without simultaneous bone lengthening with dynamic circular external fixation. It is a salvage procedure from limb amputation with correction indications and choice of patients as this is final and irreversible procedure in order to have good outcome.